Social entrepreneurship: ideas of student innovation - Kulsharipova, Z.K.; Zhilbayev, Zh.O.; Issinbayeva, K.G. (Publ.KarSU, 2017)
Social modernization as the main vector of the development of Kazakhstan's youth and business entrepreneurship is the beginning of understanding by students of the foundations of entrepreneurship as future conditions for the formation of their own business in the specialty. This article proposes the problem of activating students' knowledge about «Social entrepreneurship and how to use knowledge and skills of social entrepreneurship (JV) in the future and become an entrepreneur. Today it is known that the joint venture is intended to solve seeks to reduce social ills innovative method of constructing or combining social and economic resources so as to form a self-replicating, able to deepen the mechanism of production and the reference sample target social welfare.
Əлеуметтік кəсіпкерлік: студенттік инновациялық идеялары
Социальное предпринимательство: идеи студенческих инноваций
Keywords: entrepreneurship of business; labor potential; economic potential of the student community; the mechanism of production; social welfare